Polarization Promoted Chemical Reaction between Ba0.5Sr0.5Co0.8Fe0.2O3-δ Cathode and Ceria Based Electrolytes of Solid Oxide Fuel Cells - Yung, H.; Jian, L.; Jiang, San Ping (The Electrochemical Society, Inc, 2012)
The chemical compatibility of Ba0.5Sr0.5Co0.8Fe0.2O3-δ (BSCF) electrodes with ceria based electrolytes is investigated under solid oxide fuel cell (SOFC) operation conditions. BSCF reacts with both Ce0.9Gd0.1O1.95 (GDC) and Ce0.8Sm0.2O1.95 (SDC) at 900°C, forming barium cerate (BaxCe1-yMyO3, where M= Gd or Sm). Under cathodic current passage, the interaction between BSCF and ceria-based electrolyte takes place at temperatures as low as 700°C, forming Ba-containing particles (probably barium cerate) at the electrode/electrolyte interface. The results show that cathodic polarization promotes the chemical reaction between BSCF and ceria-based electrolyte. The accelerated reaction between BSCF and ceria is most likely related to the Ba segregation under influence of polarization and/or temperature.